Sodium Dodecylbenzene Sulfonate-Modified Biochar as An Adsorbent for The Removal of Methylene Blue - Argo Khoirul Anas; Sandy Yudha Pratama; Aqidatul Izzah; Muhammad Arsyik Kurniawan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Biochar is an interesting adsorbent material due to its use is correlated with biomass waste utilization and also minimize environmental pollution from high amount of biomass by-product. Regarding to improve the biochar ability in water treatment, several surface modifications have been developed, one of them is modification using surfactant. In this study, sodium dodecylbenzene sulfonate (SDBS) was used to modify the surface of biochar prepared from pyrolysis of cassava peels (Manihot utilissima). Its performance in biochar modification to remove methylene blue (MB) dyes was compared with sodium dodecyl sulphate (SDS) surfactant for observing the important of – interactions mechanisms. The analysis of biochar and biochar-SDBS were conducted by using Fourier transform infrared (FTIR), CHNS elemental analysis, and scanning electron microscope (SEM). Furthermore, the adsorption experiments were conducted using UV-Vis spectrophotometer. It is known that modification using SDBS could increase the adsorption capacity of biochar not only from electrostatic interaction but also through – interactions mechanisms. In this respect, as the amount of SDBS mass increased, the adsorption capacity was also improved due to the modification produced more active cites on biochar. The maximum MB adsorption onto biochar-SDBS occurred at adsorbent mass of 15 mg with optimum pH value of 10. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).